Долідження Cr(acac)3 на поверхні оксидів кремнію та алюмінію методами ТПД–МС, УФ та ІЧ спектроскопії - Davydenko, L.; Mischanchuk, B.; Pokrovskiy, V.; Babich, I.; Plyuto, Yu. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2010)
The mechanism of binding of Cr(acac)3 molecules at active sites of the surface of silica and alumina supports has been studied by temperature programmed desorption mass spectrometry (TPD-MS), UV-vis and IR spectroscopy. It has been found out that surface hydroxyl groups are responsible for binding of Cr(acac)3 molecules only in the case of silica support due to hydrogen bonding with acetylacetonate ligand. In contrast, the binding of Cr(acac)3 molecules at the alumina surface can be due to donor-acceptor interaction of π-electrons of acetylacetonate ligands with Al3+ sites.